MICROPROPAGATION OF THE ERVA-MATE THROUGH CULTURE OF NODAL SEGMENTS - ZANIOLO, Solange Ribas; ZANETTE, Flávio (Scientia Agraria, 2001)
Considering the fact that is difficult to obtain stocks from erva-mate (Ilex paraguariensis St. Hil.) by seeds, microprogation is recommended as an alternative for selected plant production. This work was carried out in the Plant Micropropagation Laboratory at the Universidade Federal do Paraná in 1991 and 1992 to establish a micropropagation protocol for erva-mate. Nodal segments were desinfested in a 0.50 or 0.75% NaOCl solution during 5, 10 or 15 min. Efficient shoot desinfestation was achieved with 0.75% NaOCl solution for 10 min, showed 20.1% contamination, 5.7% oxidation and 72.9% of the nodal segments survival. In the multiplication phase IBA and BAP combinations were tested in WPM and MS media in three subcultures. Maximum shoot regeneration was achieved when nodal segments were maintained in the three subcultures. The greatest proliferation rate (3.75 shoots/explant) was in WPM + 8.87 µM BAP. Rooting was evaluated in two steps (induction and elongation of roots) during 12 + 18 days and in one step during 30 days, with different concentrations of IBA in WPM/2 and WPM/2 + 1 g.L-1 of actived charcoal. The two steps root formation provided the greatest rooting (86.2%) and number of 8.2 roots/shoot. Development was good in plantlets rooted.